Gambaran Pemahaman Perilaku Bullying Siswa Sekolah Menengah Atas di Kota Bogor - Mayra, Zara; Alfalathi, Siti Aminah; Prabowo, Arga Satrio (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
This study aims to find out about the understanding of students and high school students in the city of Bogor, so that the results of this study can provide an overview to schools, especially to guidance and counseling teachers so that the service programs that are prepared can help schools reduce the level of bullying behavior of students in high schools in the city of Bogor. The results of this study can also provide education to students about which behaviors are included in bullying behavior. The research method used by the author is a quantitative method with a descriptive research type by collecting data through questionnaires distributed to students in the city of Bogor. The data and data sources of this study are 395 high school students in the city of Bogor using survey techniques. The instrument used for this study is a questionnaire describing bullying behavior. Data processing is done by scoring the questionnaire results of the research respondents' answers. The researcher concluded that the description of bullying behavior that the actions considered as physical bullying shown above are known to have the highest frequency of answers being strongly disagree, this means that respondents agree that they will not do things according to the statements in each variable proposed regarding physical bullying.